1966
DOI: 10.1139/m66-120
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Activity of Marine Planktonic Algae

Abstract: Cell extracts of 14 species of marine phytoplankters helonging t o six algal classes were tested for antibacterial activity against I) marine isolates and 14 strains of terreseial saprophytes inclr~ding pntential patha~ens. Aparr from iiidividual species differences, some noteworthy differences in antibiotic effectiveness were observed between the algal classes. The Batillariophyceae, Chrysophyceae, and Cq-ptophycrae showed considerably grrnter range and degree of activity than the Chlorophyceae, while the r~c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

1967
1967
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 6 publications
0
38
0
Order By: Relevance
“…Unlike metazoans, marine diatoms are not known to have an immune system that can counteract parasites. Duff et al (1966) suggested that marine diatoms can secrete antibiotics but this has not been verified by other studies. Previous reports hypothesized that DA is an anti-bacterial agent (Bates et al, 1995).…”
Section: Discussionmentioning
confidence: 87%
“…Unlike metazoans, marine diatoms are not known to have an immune system that can counteract parasites. Duff et al (1966) suggested that marine diatoms can secrete antibiotics but this has not been verified by other studies. Previous reports hypothesized that DA is an anti-bacterial agent (Bates et al, 1995).…”
Section: Discussionmentioning
confidence: 87%
“…Antibacterial activity was studied because prokaryotes represent a major group of competitors for microalgae in terms of space and resources and could also pose a threat as intracellular or epibiont parasites or direct pathogens (Cole, 1982;Imai et al, 1993;Mayali & Azam, 2004). Methanol extracts of laboratory grown cultures of P. tricornutum are known to have growth inhibitory effects in vitro against Gram-positive and Gram-negative bacteria of marine or non-marine origin (Duff et al, 1966;Kellam & Walker, 1989;Desbois et al, 2008Desbois et al, , 2009. We have shown that certain unsaturated free fatty acids are responsible for the bactericidal properties of P. tricornutum methanol extracts, namely eicosapentaenoic acid (C20:5 n-3; EPA) (Desbois et al, 2009), (6Z, 9Z, 12Z )-hexadecatrienoic acid (C16:3 n-4; HTA) and palmitoleic acid (C16:1 n-7; PA) (Desbois et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Zsochrysis galbana Parke was grown in axenic culture and the algal material was harvested and dried as described by Antia & Kalmakoff Algal extracts were prepared by three methods. Method (a) involved sequential extractions with three solvent systems (acetone ; chloroform; chloroform + methanol (I + I, v/v)) at room temperature as described by Duff et al (1966). Method (b) was similar to method (a) but with the extraction with each solvent system repeated twice before using the next solvent in the sequence.…”
Section: Methodsmentioning
confidence: 99%